The Preacher and the Practitioner in 1970s Legislative Ethics Reform: John Gardner, Richard Bolling, and Congressional Ethics. (2nd January 2020) - Stuteville, Rebekkah
Abstract : Ethics reform in the House of Representatives in the 1970s provides insight into the principles and values that influence discussions of congressional ethics today. This article explores the roles that a Missouri congressman, Richard Bolling, and the Chairman of Common Cause, John Gardner, played in advancing ethics reform in Congress. Through archival research, Bolling's years in Congress as a reformer are examined, featuring documents and correspondence from John Gardner and Common Cause. The research provides an account of their efforts to reform congressional ethics in the areas of campaign finance; conflicts of interest; lobbying disclosure; and openness. Bolling and Gardner's initiatives are assessed in light of the principles of contemporary ethics scholar Dennis F. Thompson. Thompson's values of independence, fairness, and accountability are used as an organizing framework to demonstrate the enduring nature of these values in legislative ethics.